Using electrolyzed oxidizing water combined with an ultrasonic wave on the postharvest diseases control of pineapple fruit cv. 'Phu Lae' - S. Khayankarn (2018)
The effects of ultrasound (US) and electrolyzed oxidizing (EO) water on postharvest decay of pineapple cv. Phu Lae were investigated using Fusarium sp. isolated from pineapple fruits. The effect of EO water and US irradiation on invitro growth inhibition of Fusarium sp. was studied. Spore suspensions were treated EO water with free chlorine at 100, 200 and 300ppm and different frequencies of 108, 400, 700KHz and 1MHz US irradiation for 0, 10, 30 and 60min and incubated at 27°C for 48h The study showed that all treatments of EO water totally inhibited the spore germination of the fungus. Additionally, US irradiation of 1MHz for 60min was the most effective to suppress the spore germination when compared with the control. When the fruits inoculated with Fusarium sp. were washed in EO water at 100ppm and US irradiation or combination of US and EO water significantly inhibited the decay incidence and prolonged the shelf life of the pineapple for 20 days. Treatments had no effect on fruit quality (weight loss percentage, total soluble solids, titratable acidity, pH, and ascorbic acid). The potential for EO water in combination with US in pineapple handling systems is high, due to marked synergistic effects against fungal decay of decrowned pineapple fruit during storage. © 2013 Elsevier Ltd.